2022
DOI: 10.3390/cells11233718
|View full text |Cite
|
Sign up to set email alerts
|

A Disturbed Siderophore Transport Inhibits Myxobacterial Predation

Abstract: Background: Understanding the intrinsic mechanisms of bacterial competition is a fundamental question. Iron is an essential trace nutrient that bacteria compete for. The most prevalent manner for iron scavenging is through the secretion of siderophores. Although tremendous efforts have focused on elucidating the molecular mechanisms of siderophores biosynthesis, export, uptake, and regulation of siderophores, the ecological aspects of siderophore-mediated competition are not well understood. Methods: We perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Experimentally, it has been demonstrated that depletion of iron triggers the biosynthesis of the antibiotic actinorhodin in S. coelicolor to prevent predation from M. xanthus ( Lee et al, 2020 ). Moreover, a mutant of M. xanthus that produces less siderophores (myxochelins) is defective in predation against P. aeruginosa ( Dong et al, 2022b ). Similarly, mutants in a putative TonB-dependent transporter for ferrimyxochelins and in components of the ABC transporter that introduces ferrimyxochelins into the cytoplasm also exhibit less efficient predation on this prey ( Dong et al, 2022b ).…”
Section: Role Of Metals In the Predatory Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimentally, it has been demonstrated that depletion of iron triggers the biosynthesis of the antibiotic actinorhodin in S. coelicolor to prevent predation from M. xanthus ( Lee et al, 2020 ). Moreover, a mutant of M. xanthus that produces less siderophores (myxochelins) is defective in predation against P. aeruginosa ( Dong et al, 2022b ). Similarly, mutants in a putative TonB-dependent transporter for ferrimyxochelins and in components of the ABC transporter that introduces ferrimyxochelins into the cytoplasm also exhibit less efficient predation on this prey ( Dong et al, 2022b ).…”
Section: Role Of Metals In the Predatory Interactionmentioning
confidence: 99%
“…Moreover, a mutant of M. xanthus that produces less siderophores (myxochelins) is defective in predation against P. aeruginosa ( Dong et al, 2022b ). Similarly, mutants in a putative TonB-dependent transporter for ferrimyxochelins and in components of the ABC transporter that introduces ferrimyxochelins into the cytoplasm also exhibit less efficient predation on this prey ( Dong et al, 2022b ). All these data seem to indicate that competition for iron plays a decisive role in the myxobacterial predatory interaction with the prey.…”
Section: Role Of Metals In the Predatory Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…This complex formation is facilitated by specific transport proteins that transfer siderophores from inside the cell to the outside, creating soluble complexes with iron ions. These complexes are then recognized and absorbed by the microbial uptake system [52]. Once inside the cell, iron ions are dissociated from the siderophores through two primary methods [53].…”
Section: Secretion and Mechanism Of Action Of Siderophoresmentioning
confidence: 99%